2015
DOI: 10.1177/1354856515579837
|View full text |Cite
|
Sign up to set email alerts
|

Sound, materiality and embodiment challenges for the concept of ‘musical expertise’ in the age of digital mediatization

Abstract: Within academic music research, 'musical expertise' is often employed as a 'moderator variable' when conducting empirical studies on music listening. Prevalent conceptualizations typically conceive of it as a bundle of cognitive skills acquired through formal musical education. By implicitly drawing on the paradigm of the Western classical live concert, this ignores that for most people nowadays, the term 'music' refers to electro-acoustically generated sound waves rendered by audio or multimedia electronic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(37 reference statements)
0
1
0
1
Order By: Relevance
“…For example, some authors have shown that ICT can help students focus on their own body as a source of expressivity, self-control, and reflection (e.g., Boucher et al., 2019 ). Others have insisted that the use of ICT in music teaching can aid the development of communication skills and social interaction (e.g., Serrano, 2017 ), the ability to process feedback ( Guerrero, 2014 ; Lepa et al., 2015 ), overall creativity and musical composition ( Freedman, 2013 ), and even performance on certain instruments ( Cano et al., 2014 ; Chao-Fernandez et al., 2017 ).…”
Section: The Use Of Digital Technologies In Music Classrooms: Transformation or Reproduction?mentioning
confidence: 99%
“…For example, some authors have shown that ICT can help students focus on their own body as a source of expressivity, self-control, and reflection (e.g., Boucher et al., 2019 ). Others have insisted that the use of ICT in music teaching can aid the development of communication skills and social interaction (e.g., Serrano, 2017 ), the ability to process feedback ( Guerrero, 2014 ; Lepa et al., 2015 ), overall creativity and musical composition ( Freedman, 2013 ), and even performance on certain instruments ( Cano et al., 2014 ; Chao-Fernandez et al., 2017 ).…”
Section: The Use Of Digital Technologies In Music Classrooms: Transformation or Reproduction?mentioning
confidence: 99%
“…En un nivel profesional, las tecnologías digitales suponen un gran avance y un replanteamiento de lo que hasta ahora eran los tradicionales conciertos pedagógicos y la recepción de la música (Lepa, Hoklas, Egermann y Weinzieri, 2015). Con esto, se puede afirmar que se cierra el círculo.…”
Section: Formación Habilitanteunclassified